FvbHLH1 Regulates the Accumulation of Phenolic Compounds in the Yellow Cap of Flammulina velutipes - Jiangyi Zeng; Dingding Shi; Ying Chen; Xuemei Bao; Yuan Zong (Journal of Fungi, 2023)
Flammulina velutipes is a renowned edible and medicinal fungus. Commercially cultivated F. velutipes occurs in two distinct phenotypes: white and yellow. However, the underlying mechanism contributing to the yellow phenotype and high nutritional value remain uncertain. We reconfirmed that the browning process in F. velutipes is attributable to melanin accumulation, although the initial yellow cap seemed unrelated to melanin. A transcriptomic and metabolomic joint analysis revealed that 477 chemical compounds categorized into 11 classes, among which 191 exhibited significantly different levels of accumulation between different phenotypes. Specifically, 12 compounds were unique to the yellow F. velutipes, including ferulic acid, and 3-Aminosalicylic acid. Free fatty acids and xanthine were identified as the primary compounds correlating with the yellow and oily cap. A total of 44,087 genes were identified, which were more homologous to Pleurotus ostreatus PC15. Structural genes such as PAL (phenylalanine ammonialyase), C4H (cinnamate 4-hydroxylase), C3H (Coumarin-3-hydroxylase), AoMT (caffeoyl coenzyme A-O-methyltransferase), and 4CL (4-coumarate: CoA ligase) were up-regulated, thereby activating the lignin biosynthesis and metabolism pathway. Additionally, FvbHLH1 can lead to the consumption of a huge amount of phenylalanine while generating flavonoids and organic acid compounds. Meanwhile, ferulic acid biosynthesis was activated. Therefore, this study clarifies the chemical and molecular bases for the yellow phenotype and nutritional value of F. velutipes.